Integrated System for Hydraulic Simulations - Nguyen, Giang; Šipková, Viera; Krammer, Peter; Hluchý, Ladislav; Dobrucký, Miroslav; Tran, Viet; Habala, Ondrej (Computing and Informatics, 2016)
The work described in this paper is aimed at applying and co-operating of modern information technologies and mathematical modeling to make a risk analysis of the water-supply in big cities. It is instrumental in the investigation of the hydraulics of water-supply systems using the simulation model EPANET executed on the underlying high-performance computing infrastructure. The simulation process is integrated with the GIS environment in order to correct input data and visualize the simulation output. Input data for the model can be modified directly within the designed scientific gateway which enables hydraulic domain experts to interact comfortably with the HPC capacity. Furthermore, the system includes some data mining capabilities forming bridges between the hydraulic data storage and available hydrological measurements focused on water consumption modeling and predictions. In simulating the main emphasis is given to optimize the measure of a similarity between the mathematical model and the real system in order to obtain reliable results.